Innovative Processing of Local Ginger's Superior Products into Instant Ginger Drink in Samosir Regency - Sheryl Valencia Pangaribuan; Elisabeth Fitryany Manik; Harry Jaya Pramana; Jacob Kuntuy (Outline Journal of Economic Studies, 2026)
Purpose: This study aims to analyze the potential of ginger (Zingiber officinale) as a superior regional commodity in Samosir Regency, North Sumatra, and to formulate development strategies for value-added processed products in the form of instant ginger drink. Methods: This research uses a descriptive quantitative approach. The analytical tools applied are the Location Quotient (LQ) to identify the comparative advantage of ginger among agricultural commodities in Samosir Regency, and SWOT analysis to evaluate internal and external factors affecting the development of instant ginger drink products. Results: The analysis shows that ginger has an LQ value of 2.117, indicating that it is a comparatively superior commodity in the region. The SWOT analysis identifies key strengths of instant ginger drink products, including ease of preparation and recognized health benefits. Conclusions: The development of instant ginger drink has strong potential to increase the added value of ginger production, improve farmers’ income, strengthen the local economy, and encourage diversification of horticultural products in Samosir Regency. Originality: This study combines LQ and SWOT analyses to assess both the regional superiority of ginger and strategic opportunities for developing value-added ginger-based products.